Pemisahan Ion Krom(III) dan Krom(IV) Dalam Larutan Dengan Menggunakan Biomassa Ganggang Hijau Spirogyra subsalsa Sebagai Biosorben. - Mawardi, Mawardi; Munaf, E.; Kosela, S.; Wibowo, Widayanti (Bumi Lestari; Vol 14 No 2 (2014))
Characteristic of biosorption of chromium(III) and chromium(VI) by green ganggange Spirogyra subsalsa sp. biomass was investigated in a batch system. Based on FTIR spectroscopy spectra can be concluded that the biomass of green ganggange S. Subsalsa containing carboxylate groups, amines, amides, amino, carbonyl and hydroxyl, in addition to the compounds of silicon, sulfur and phosphorus. The results showed that the capacity biosorpsi strongly influenced by solution pH, contact time and initial concentration of the solution. The maximum sorption of Cr 3+ cations was seen at pH 4,0 and than constant at the higher pH. Biosorption of Cr6+, exist as Cr2O72- anion, decrease by increase of solution pH. The maximum biosorption capacity for Cr3+ and Cr ions are 1.82 mg (0.035 mmol) and 1.51 mg (0.029 mmol) per gram of dry biomass, respectively.  Rate of biosorption is relatively fast, with long intervals of 30 minutes, each ion is absorbed approximately 95.7% and 86.5%. Absorption is also influenced by rapid mixing of biomass, while the factors of particle size and heating biosorben biomass absorption is less affected.
Keywords: biosorption, spirogyra subsalsa, chromium(III), chromium(VI), batch System